Effects of scutellarin on the mechanism of cardiovascular diseases: a review - Zhang, Xinyu; Yin, Tong; Wang, Yincang; Du, Jiazhe; Dou, Jinjin; Zhang, Xiwu (Frontiers in Pharmacology, 2024)
Cardiovascular diseases represent a significant worldwide problem, jeopardizing individuals' physical and mental well-being as well as their quality of life as a result of their widespread incidence and fatality. With the aging society, the occurrence of Cardiovascular diseases is progressively rising each year. However, although drugs developed for treating Cardiovascular diseases have clear targets and proven efficacy, they still carry certain toxic and side effect risks. Therefore, finding safe, effective, and practical treatment options is crucial. Scutellarin is the primary constituent of Erigeron breviscapus (Vant.) Hand-Mazz. This article aims to establish a theoretical foundation for the creation and use of secure, productive, and logical medications for Scutellarin in curing heart-related illnesses. Additionally, the examination and analysis of the signal pathway and its associated mechanisms with regard to the employment of SCU in treating heart diseases will impart innovative resolving concepts for the treatment and prevention of Cardiovascular diseases.